A hazard index for roadside of two-lane rural roads (2014)
Roadside areas are elements intended to reduce the Run-off-road crashes. The hazardousness is an indicator of compliance of this objective. There are few methods to measure hazardousness, which usually depend of the availability of accident data. This paper examines the factors that explain the roadside hazardousness on the basis of existing models and analysis of field data. It was determined that the clearance side next to the barriers of protection, especially in curves with inclined slopes, it is significant to explain the hazards. It was determined that for straights and curves without barriers is relevant the type of object and its position measured position in the roadside.